SnAP Edu: learn while playing / Azlina Mohd Mydin, Wan Anisha Wan Mohammad and Rafizah Kechil - Mohd Mydin, Azlina Mohd Mydin; Wan Mohammad, Wan Anisha; Kechil, Rafizah (Unit Penerbitan JSKM, 2023)
SnAP Edu is card game that create as a new tactic of learning in an interesting way thru playing. As in the era of internet and globalization, teacher and student must explore many other approaches in studying and doing revisions that up to trends. Learning and revision process using gaming will increase the student understanding. This card game are created to help student to do learning and revision process interesting and enjoyable. SnAP Edu game card can be used to any level of education either for schools or higher-level institution. This card game is design to be played from 2 to maximum of 6 players. The design of these cards is colorful and using flower images. The players have to answer question asked based on the same card that been snapped. The winner in the game calculated based on the large number of card s collected. The question asked are based on the topic selected before the game starts. A group of around 30 students from standard 3 to 5 are used as sample of respondents for these studies. The result shows the players felt enjoy, interesting and easy to do revision while playing this SnAP Edu card game